Tsetse fly microbiota: form and function - Wang, Jingwen; Weiss, Brian L.; Aksoy, Serap (Frontiers in Cellular and Infection Microbiology, 2013)
Tsetse flies are the primary vectors of African trypanosomes, which cause Human and Animal African trypanosomiasis in 36 countries in sub-Saharan Africa. These flies have also established symbiotic associations with bacterial and viral microorganisms. Laboratory-reared tsetse flies harbor up to four vertically transmitted organisms - obligate Wigglesworthia, commensal Sodalis, parasitic Wolbachia and Salivary Gland Hypertrophy Virus (SGHV). Field-captured tsetse can harbor these symbionts as well as environmentally acquired commensal bacteria. This microbial community influences several aspects of tsetse’s physiology, including nutrition, fecundity and vector competence. This review provides a detailed description of tsetse’s microbiome, and describes the physiology underlying host-microbe, and microbe-microbe, interactions that occur in this fly.